New cytotoxic cucurbitacins from Wilbrandia ebracteata Cogn - Lang, Karen L. (2011)
Chemical investigation of the roots of Wilbrandia ebracteata Cogn. (Cucurbitaceae) led to the isolation of two new (12) and four known (36) cucurbitacins. Their structures were elucidated by NMR and MS and compared with related compounds. The in vitro cytotoxicity of isolated compounds was evaluated against RD, KB, HCT-8, and A549 cell lines showing strong activity.